Teaching Performance Instruments of Physical Education Teachers - Lumba, Andreas J. F.; Blegur, Jusuf; Bayu, Wahyu Indra (LPPM Undiksha, 2021)
A teacher's teaching performance will determine the success of learning. However, the main problem in developing teacher teaching performance lies in the